2018
DOI: 10.1002/anie.201809954
|View full text |Cite
|
Sign up to set email alerts
|

A Clade II‐D Fungal Chimeric Diterpene Synthase from Colletotrichum gloeosporioides Produces Dolasta‐1(15),8‐diene

Abstract: Based on at erpenoid overproduction platform in yeast for genome mining,achimeric diterpene synthase from the endophytic fungus Colletotrichum gloeosporioides ES026 was characterized as the (5R,12R,14S)-dolasta-1(15),8-diene synthase.T he absolute configuration was independently verified through the use of enantioselectively deuterated terpene precursors,w hichu nequivocally established the predicted C1-III-IV cyclization mode for this first characterized clade II-D enzyme.Extensive isotopic labeling experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 43 publications
0
41
0
12
Order By: Relevance
“…The similarity of the active site architectures among AaTPS and other terpene synthases suggests that the aromatic prenyltransferase activity discovered for AaTPS might be a ubiquitous phenomenon in the greater family of class I terpene cyclases. To explore this possibility, the terpene cyclases FgFS, FgJ01056 (longiborneol synthase from F. graminearum ), FgJ09920 (koraiol synthase from F. graminearum ), FgGS, FgMS, and CgDS, which had been previously characterized in our lab 11 , 13 , 14 , 35 , and the plant-derived taxadiene synthase (TXS) 26 were selected for in vitro assay. The resulting data reveal that when incubated with DMAPP and indole, all of these terpene cyclases except FgMS produced prenylindoles 5 – 10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of the active site architectures among AaTPS and other terpene synthases suggests that the aromatic prenyltransferase activity discovered for AaTPS might be a ubiquitous phenomenon in the greater family of class I terpene cyclases. To explore this possibility, the terpene cyclases FgFS, FgJ01056 (longiborneol synthase from F. graminearum ), FgJ09920 (koraiol synthase from F. graminearum ), FgGS, FgMS, and CgDS, which had been previously characterized in our lab 11 , 13 , 14 , 35 , and the plant-derived taxadiene synthase (TXS) 26 were selected for in vitro assay. The resulting data reveal that when incubated with DMAPP and indole, all of these terpene cyclases except FgMS produced prenylindoles 5 – 10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we established robust platforms in Escherichia coli and Saccharomyces cerevisiae to accelerate the discovery of C 20 diterpene and C 25 sesterterpene natural products with diverse molecular structure and stereochemistry 10 , 11 . These studies led to the discovery and characterization of the terpene cyclases Fusarium graminearum mangicdiene synthase (FgMS), F. graminearum GJ1012 synthase (FgGS), F. graminearum fusariumdiene and fusagramineol synthase (FgFS), and Colletotrichum gloeosporioides dolasta-1(15),8-diene synthase (CgDS); the products generated by each of these enzymes were systematically characterized 11 14 . Since our report of these class I terpene cyclases, we further probed their functional properties and we encountered an unexpected surprise—we discovered substantial cryptic aromatic prenyltransferase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from B , a 2,7-ring closure and deprotonation at the same carbon atom gives α-longipinene ( 6 ). For the main product 1 , the deprotonation was followed by an incubation of HcS and FPPS with (2- 2 H)GPP [39] and IPP, which resulted in unlabelled 1 as observed by GC–MS (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Previously characterised enzymes are shown in green, the enzyme characterised in this study is shown in red. AcOS: Aspergillus clavatus ophiobolin F synthase, CgDS: Colletotrichum gloeosporioides dolasta‐1(15),8‐diene synthase, EvAS: E. variecolor astellifadiene synthase, EvQS: E. variecolor quiannulatene synthase, EvSS: E. variecolor stellata‐2,6,19‐triene synthase, EvVS: E. variecolor variediene synthase, FgMS: F. graminearum mangicdiene synthase, NfSS: Neosartorya fischeri sesterfisherol synthase, PaFS: P. amygdali fusicocca‐2,10(14)‐diene synthase, PaPS: P. amygdali phomopsene synthase, PbSS: Penicillium brasilianum sesterbrasiliatriene synthase, PcCS: P. chrysogenum cyclopiane‐type diterpene synthase, PvPS: Penicillium verruculosum preasperterpenoid A synthase …”
Section: Methodsmentioning
confidence: 99%